1970
DOI: 10.3126/saarctb.v8i2.5896
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization And Comparison Of Multi Drug Resistant Strains Of Mycobacterium Tuberculosis By Phenotypic And Genotypic Method

Abstract: Introduction: Drug resistant tuberculosis is a signifi cant threat to tuberculosis control because only a few effective drugs are available against M. tuberculosis. The aims of this study were to compare multi drug resistant (MDR) strains of tuberculosis by phenotypic and genotypic method and determine type, location and frequency of rpoB and KatG gene mutations. Methodology: Anti-tuberculosis drugs susceptibility test of M. tuberculosis grown on Lowenstein Jensen medium was performed by proportion method. MDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…A study by Negi et al, in India revealed KatG S315T mutation in 74.19% of strains of MTB from Delhi [36]. Similar study conducted by Bhatt CP et al, in Nepal revealed point mutation in 9 (45%) new and 8 (40%) old PTB cases from 20 MDR-TB strains [8].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A study by Negi et al, in India revealed KatG S315T mutation in 74.19% of strains of MTB from Delhi [36]. Similar study conducted by Bhatt CP et al, in Nepal revealed point mutation in 9 (45%) new and 8 (40%) old PTB cases from 20 MDR-TB strains [8].…”
Section: Discussionmentioning
confidence: 53%
“…The complete genome of M.tuberculosis strains has been mapped as a length of about 4.4Mb, however each gene of M.tuberculosis may have separate function including the specific complex formation with important drugs being used as tuberculosis treatment regime. Unusual genetic alteration of drug resistance [8].…”
Section: Introductionmentioning
confidence: 99%